Video‐assisted thoracic surgery for the management of pyothorax in dogs: 14 cases. Issue 5 (29th April 2017) - Scott, Jacqueline; Singh, Ameet; Monnet, Eric; Coleman, Kristin A.; Runge, Jeffrey J.; Case, Joseph Brad; Mayhew, Philipp D.
Abstract: Objective: To report the perioperative findings and outcome of dogs undergoing video‐assisted thoracic surgery (VATS) for the management of pyothorax. Design: Multi‐institutional, retrospective study. Animals: Client‐owned dogs (n = 14). Methods: Medical records of dogs with pyothorax managed via VATS were reviewed for signalment, history, clinical signs, clinicopathological findings, diagnostic imaging results, surgical variables, bacterial culture and sensitivity results, post‐operative management and outcome. VATS was performed after placing a paraxyphoid endoscopic portal and 2‐3 intercostal instrument portals. VATS exploration was followed by one or more of the following: mediastinal debridement, tissue sampling, pleural lavage, and placement of a thoracostomy tube. Results: Two dogs (14%) required conversion from VATS to an open thoracotomy to completely resect proliferative mediastinal tissue. These dogs had severe pleural effusion on preoperative thoracic radiographs and one had severely thickened contrast‐enhancing mediastinum on preoperative computed tomography (CT). The cause of pyothorax was identified as a penetrating gastric foreign body (n = 2), migrating plant material (n = 2), and idiopathic (n = 10). The median follow‐up time was 143 days (range, 14‐2402 days). All dogs were discharged from the hospital and their clinical signs resolved. One patient had recurrence of a pyothorax requiring revision surgery 17 months postoperatively. Conclusion: VATS allows minimally invasive treatment of uncomplicated canine pyothorax. Preoperative thoracic CT may help identify candidates for VATS among dogs with pyothorax.